Analysis and Application of the Mechanical Properties of the Karst Collapse Column Fillings. (5th April 2021) - Lin, Zhibin; Zhang, Boyang; Gong, Xiaofei; Sun, Limin; Wang, Wenzhen; Yang, Dafang; Yang, Yanlin; Guo, Ming; Pan, Xia-Hui
Abstract : The filling material of the karst collapse column (KCC) is easy to be activated by mining. During this process, the mechanical properties of KCC fillings change, and its water resisting capacity constantly deteriorates and thus often leads to water inrush disaster. In this study, the samples of KCC fillings were taken on-site and then were remolded by the consolidation drainage method. The variation laws of the compressive strength, tensile strength, cohesive stress, internal friction angle, and permeability of the filling samples with respect to the consolidation pressure and moisture content were tested and analyzed. Based on an engineering example, the yield and activation and particle loss of the filling material of the KCC are analyzed. A mechanism for the lagging water inrush of KCC in the process of mining is proposed. The main results of the present study can be concluded concisely as follows. (1) The KCC fillings show obvious soft rock characteristics in the process of uniaxial compression and Brazilian split. The ratio of the uniaxial compressive strength to splitting tensile strength is between 12 : 1 and 8 : 1. The larger the consolidation pressure or the smaller the moisture content, the larger the ratio. (2) With the increase of consolidation pressure or the decrease of moisture content, the uniaxial compressive strength, elastic modulus, splitting tensile strength, cohesive stress, and internal friction angle of the filling material of the KCC increase linearly, while its permeability increases exponentially. (3) When the crack field of the surrounding rocks of the stope is connected with the KCC, its filling material will continue to yield, activate, and migrate under the fluid-solid coupling effect and finally result in the lagging water inrush from the KCC.